Identity in Nigerian hip-hop music - Temitope Michael Ajayi; Oluwatunmise Omoniyi Olupona (Journal of Language and Pragmatics Studies, 2026)
Nigerian hip hop music genre has been explored with different thematic foci. However, not much attention has been given to how hip-hop artistes in the country create and project different identities for themselves through the ideologies expressed in their songs. This study, therefore, within the purview of Critical Discourse Analysis, investigates how hip-hop artistes in Nigeria create and exhibit different identities through the ideological orientations displayed in their songs. Findings reveal Nigerian hip hop artistes, through their lyrics, create and project themselves as theists, custodians of culture, and a people with a rich linguistic repertoire.